PENDAMPINGAN KETERAMPILAN BERPIDATO PADA NASYIATUL AISYIYAH CABANG PADANGSIDIMPUAN SELATAN - Eli Marlina Harahap; Nur Afifah; Khatib Lubis; Nikmah Sari Hasibuan (Politeknik Negeri Sriwijaya, 2021)
Giving a speech is one of the activities to speak or communicate verbally. The purpose of the implementation of this activity is to train Nasyiatul Aisyiyah's South Padangsidimpuan branch in speaking skills. By conducting this training, Nasyiatul Aisyiyah will be more skilled in making speeches in front of the public, therefore follow-up is needed to continue to practice Nasyiatul Aisyiyah's speech skills. There are 4 stages in providing speech training assistance, namely starting from the preparation stage, the training implementation stage, the evaluation stage and the followup stage. The results of the speech skills assistance to Nasyiatul Aisyiyah received a good response from the partners. The partners play an active role in participating in the speech skills training